Efficient sex hormone biosensors in Saccharomyces cerevisiae cells to evaluate human aromatase activity and inhibition - Jie Wu; Matthias Bureik; Mario Andrea Marchisio (Scientific Reports)
Abstract Yeast sex-hormone whole-cell biosensors are analytical tools characterized by long-time storage and low production cost. We engineered compact β-estradiol biosensors in S. cerevisiae cells by leveraging short (20-nt long) operators bound by the fusion protein LexA-ER-VP64—where ER is the human estrogen receptor and VP64 a strong viral activation domain. Our best biosensors showed high accuracy since their recovery concentration ranged between 97.13% and 104.69%. As a novelty, we built on top of them testosterone biosensors that exploit the conversion of testosterone into β-estradiol by the human aromatase enzyme—expressed in S. cerevisiae together with its co-factor CPR. We used our engineered yeast strains to evaluate aromatase activity through fluorescence measurements without the need for protein purification. Besides, we set up an aromatase-inhibitors evaluation assay to measure the IC50 (half-maximal inhibitory concentration) of candidate inhibitory compounds and developed a screening assay for enzymes that metabolize β-estradiol that demands only to measure fluorescence. These two assays allow the screening of a large number of chemicals and proteins in a fast and economic fashion. We think that our work will facilitate considerably high throughput screening for the discovery of new drugs and unknown metabolic processes.